Sonographic Correlation of Fetal Foot Length as a Reliable Parameter for Estimation of Gestational Age in the Second and Third Trimester of Pregnancy - Shahid, Kiran; Khan, Nasir; Ayub, Hafiz Muhammad Ahsan (Biological and Clinical Sciences Research Journal, 2025)
Accurate estimation of gestational age is essential for appropriate antenatal care and fetal assessment. Standard ultrasonographic parameters may be affected in certain clinical situations, so that fetal foot length may serve as an additional reliable biometric marker. Objective: To determine the correlation between fetal foot length and standard biometric parameters, including femur length, biparietal diameter, and abdominal circumference, for the estimation of gestational age during the second and third trimesters of pregnancy. Methods: This cross-sectional study was conducted in the Department of Radiology, Holy Family Hospital, Rawalpindi, from 20 March 2023 to 19 September 2023. A total of 120 pregnant women in the second or third trimester undergoing ultrasonographic assessment were enrolled. Pregnancies complicated by oligohydramnios, polyhydramnios, intrauterine growth restriction, and skeletal dysplasia were excluded. Transabdominal ultrasonography was performed for all participants. Fetal foot length was measured and compared with conventional fetal biometric parameters, including femur length, biparietal diameter, and abdominal circumference, to assess their correlation with gestational age. Data were entered and analyzed using SPSS version 26. Descriptive statistics were calculated, and inferential analysis was performed using correlation testing. A p-value of less than 0.05 was considered statistically significant. Results: Among 120 participants, the mean maternal age was 28.28±4.37 years, while the mean gestational age was 27.33±4.99 weeks. The mean fetal foot length was 47.87±11.88 mm, the mean femur length was 51.29±12.58 mm, the mean biparietal diameter was 69.09±14.05 mm, and the mean abdominal circumference was 231.73±51.77 mm. Fetal foot length showed a significant positive correlation with gestational age and with other fetal biometric parameters (p<0.0001). The correlation coefficient of fetal foot length was 0.867 with femur length, 0.850 with biparietal diameter, and 0.743 with abdominal circumference, all of which were statistically significant (p<0.0001). Conclusion: Fetal foot length demonstrated a strong positive correlation with gestational age and standard fetal biometric parameters in the second and third trimesters. It may be considered a reliable supplementary parameter for gestational age estimation in routine obstetric ultrasonography.